OP0208 A proof-of-concept double-blind randomised placebo-controlled trial of probiotics in systemic sclerosis associated gastrointestinal disease. (12th June 2018) - Low, A.H.L.; Teng, G.G.; Pettersson, S.; De Sessions, P.F.; Fan, Q.; Law, A.; Santosa, A.; Lim, A.; Thumboo, J.
Abstract : Background: Hypothesis: Gastrointestinal (GI) microbiota is a co-founding factor contributing to systemic sclerosis (SSc) and GI manifestations. Probiotics reduced GI symptoms by modulating microbiome composition in an open-label study. 1 Objectives: To determine whether probiotics result in reduction of GI symptoms in SSc patients, assessed using the UCLA Gastrointestinal Tract questionnaire (GIT 2.0). Methods: In this double-blind placebo-controlled trial, 40 subjects with SSc (total GIT0.1) were randomised to receive 60 days of probiotics (900 billion units/day, composite of lactobacilli, bifidobacteria and streptococcus) or placebo, followed by 60 days of probiotics in both groups. Subjects on probiotics or antibiotics 30 days prior were excluded. Enrolled subjects were required to have stable doses of prednisolone, immunosuppression and GI medications 30 days prior and during the trial. Between group differences in total GIT change was assessed after 60 days (primary endpoint) and 120 days (secondary endpoint). Stool microbiome composition was analysed using 16S next generation sequencing. We performed principle coordinate analysis, alpha diversity and taxonomic level analyses. Two-sample t-tests were used to evaluate between-group differences, reported as mean ±SD. An intention-to-treat and last observer carried forward analysis was done. P-value<0.05 was considered statistically significant. Results: 40 subjects were randomised to placebo (n=21) or probiotics (n=19). Baseline characteristics are summarised in table 1. At the primary endpoint, change in total GIT was not statistically significant between placebo (−0.14±0.27) and probiotic groups (−0.13±0.31; p=0.85). At the secondary endpoint, there was greater reduction in total GIT in the probiotic (n=13; −0.18±0.26) than the initial placebo group (n=15; −0.05±0.22), though not reaching statistical significance (p=0.14). There was a statistically significant reduction in GIT-reflux subdomain in the probiotic group (−0.22±0.16 vs initial placebo group 0.05±0.27; p=0.0037). Subjects on probiotics had greater abundance of lactobacillus, bifidobacterium and streptococcus, and exhibited high alpha diversity, whereas those on placebo had a decreasing trend of alpha diversity. Majority of adverse events were grades I and II. Conclusions: This trial demonstrated safety of probiotics in SSc. The primary outcome at 60 days was not achieved. A prolonged course of probiotics (120 days) resulted in greater improvement of GI reflux. There was a possible positive association between reduced GI stress (evidenced by greater alpha diversity of the GI microbiota) and lower GIT scores in the probiotic group. This study provides justification for a larger definitive trial of probiotics in SSc. Reference: [1] Frech TM, Khanna D, Maranian P, et al. Probiotics for the treatment of systemic sclerosis-associated gastrointestinal bloating/distention. Clin Exp Rheumatol2011;29(2 Suppl 65):S22–25. Disclosure of Interest: None declared